PENGARUH PENERAPAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CITRA PERUSAHAAN (Kasus Pada Masyarakat Sekitar Kantor Pusat PT.Perkebunan Nusantara V Pekanbaru) - Wiwik Agustia Ningsih; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted at the PT.Perkebunan Nusantara V Pekanbaru, the study aimas to determine the effect of the application of CSR programs to company image. Applications of CSR programs as an independent variable (X), while the company image as the dependent variable (Y).The research methods uses descriptive and analysis using SPSS, where the sample is people around the central office PT.Perkebunan Nusantara V Pekanbaru there are 100 respondents. Results from this study indicate that the implementation of CSR programs and significant positive effect on the iamge of the archipelago PT.Perkebunan Nusantara V Pekanbaru. Based on the identification of determinants shows that R square of 59,7%, which means that company’s image PT.Perkebunan Nusantara V Pekanbaru effect by the variable application of CSR programs by 59,7% and the remaining 40,3% is influenced by other variable that are not used in this study.Keywords: Implementation of CSR programs and corporate image